Chapter IX. The Demands of Students, Youth Organizations and the Writers' Union Presented between 18 and 23 October 1956 - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. First draft of section C of chapter IX.